Relationship between Education Level of Health Workers and Perception of Physiotherapy Needs in Malang City Health Center - Lubis, Zidni Imanurrohmah; Hyasintha, Nadya Fawwaz; Yulianti, Atika (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: This study aims to analyze the relationship between the education level of health workers and their perceptions of physiotherapy needs at Puskesmas Malang City. Perception, which is an individual's view or understanding of an object, is influenced by various factors, including education level. Methods: The method used was a quantitative approach with data collection through questionnaires distributed to health workers at the health center. Data analysis was conducted using the Chi-Square test to identify the relationship between education level and perception of physiotherapy needs. Results: The results showed that the significance value (p) was 0.439, which means p> 0.05, so there was no significant relationship between education level and perception of physiotherapy needs. Although most health workers had positive perceptions, this finding suggests that education did not directly influence their perceptions. Conclusion: This suggests that although education can improve knowledge, other factors such as work experience, training, and social environment also play a role in shaping health workers' perceptions of physiotherapy. This study is expected to provide useful information for the development of education and training programs for health workers in improving their understanding of physiotherapy, as well as encouraging better collaboration in health services.